Wear characteristics of aluminium matrix composites reinforced with Si-based refractory compounds derived from rice husks. Issue 1 (1st January 2020) - Adediran, Adeolu Adesoji; Alaneme, Kenneth Kanayo; Oladele, Isiaka Oluwole; Akinlabi, Esther Titilayo
Abstract: This study investigates the wear behaviour of aluminium metal matrix composites reinforced with 10 wt.% Si-based refractory compounds (SBRC) derived from rice husk (RHs). The wear test was conducted using a pin-on-disk tribometer under varying loads with a fixed sliding distance. Scanning electron microscope was used to characterize the worn-out surface and the wear debris. From the results obtained, as the applied load increases, the coefficient of friction (CoF) value reduces to a significant extent. This reduction might be associated with the presence of graphite phase in all the composites developed. The results showed that for samples subjected to 5 N load, T1650 had the optimum value of wear volume amounting to 25–93% increase in wear volume against other samples. Additionally, for 8 N load, K1650 showed a higher response in wear volume having 26–74% improvement in wear volume. The specific wear rate of the composites developed at 5 N load application can be ranked in the following order: T1600 > K1250 > T1650 > K1650 > T1250. A severe agglomeration, possibly caused by fragmentation of the clustered debris, dominated the morphology of the worn-out surface. From the EDS spectra, the iron content appears to be low while the oxygen content very high, this is an indication that the tribolayer island was oxidized. An optical photograph showing the wear profile was also taken. It is inferred that the initial wear mechanism of the composites is adhesive, this later converted to abrasive.